2021
DOI: 10.1021/acsanm.0c02993
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-Incorporated Carbon Nanodots for T1-Weighted Magnetic Resonance Imaging

Abstract: The design and the development of contrast agents for magnetic resonance imaging (MRI), with improved chemical stability and higher contrasting capability for clinical translation, compared to conventional contrast agents, is still of great interest. In this study, a facile and universal approach was explored for controllable functionalization of red-emissive carbon nanodots (RCNDs) with diethylenetriaminepentaacetic anhydride (DTPA) for chelation of gadolinium. A series of accurate characterizations were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The Bi,Gd-CQD longitudinal relaxivity value ( r 1 ) is 4.29 mM −1 s −1 calculated from the slope of the fitting line, which is significantly larger than that of the commercial T1-weighted contrast agent (Gd-DTPA, r 1 = 3.40 mM −1 s −1 ). 52 This demonstrates that Bi,Gd-CQDs contact water molecules more effectively than Gd-DTPA. Table S2 (ESI†) shows the MRI performance of different Gd-doped nanoparticles compared with other reports.…”
Section: Resultsmentioning
confidence: 92%
“…The Bi,Gd-CQD longitudinal relaxivity value ( r 1 ) is 4.29 mM −1 s −1 calculated from the slope of the fitting line, which is significantly larger than that of the commercial T1-weighted contrast agent (Gd-DTPA, r 1 = 3.40 mM −1 s −1 ). 52 This demonstrates that Bi,Gd-CQDs contact water molecules more effectively than Gd-DTPA. Table S2 (ESI†) shows the MRI performance of different Gd-doped nanoparticles compared with other reports.…”
Section: Resultsmentioning
confidence: 92%
“…A decrease in relaxation times of T 1 was observed as the Gd 3+ concentration increased, consistent with the rise in the relaxation rate R 1 due to the presence of paramagnetic species. This relationship can be described by the formula R 1obs = R 1int + ρ 1 [Gd 3+ ], where R 1obs represents the observed relaxation rate, R 1int is the relaxation rate in the absence of added paramagnetic species, ρ 1 is the longitudinal relaxivity, and [Gd 3+ ] is the Gd concentration. , To determine the relaxivity of ρ 1 , the relaxation rate R 1 was linearly fitted against the Gd 3+ concentration (Figure d). The relaxivity values were found to be 5.0 ± 1.1 mM –1 s –1 at pH 7.4, 6.1 ± 0.7 mM –1 s –1 at pH 6.4, and 11.3 ± 0.2 mM –1 s –1 at pH 5.5.…”
Section: Results and Discussionmentioning
confidence: 99%
“…CNDs were obtained from a method from our previous reports. [ 13 ] In brief, CNDs were prepared by hydrothermal treatment of PPA. 20 mg of PPA were dispersed in 40 mL of NaOH solution (1 mM).…”
Section: Methodsmentioning
confidence: 99%
“…[ 11 ] As an example, we previously demonstrated that a targeted intracellular production of ROS could be successfully achieved in tumor cells using folic acid (FA)‐modified photoactive CNDs, [ 12 ] while the covalent functionalization of gadolinium to CND surface allowed multimodal bioimaging. [ 13 ] Chlorin e6 (Ce6) is a second‐generation PS with a high efficacy and low dark toxicity, but its extremely poor water solubility and instability hamper its clinical use. [ 14 ] The combined irradiation of both CNDs and Ce6 could enhance the ROS generation, thus boosting the whole PDT efficiency.…”
Section: Introductionmentioning
confidence: 99%